UPAYA PENCEGAHAN STUNTING DENGAN MENINGKATKAN KONSUMSI DAUN KELOR - Auradian Marta; Althoof Eka Putra; Awang Buana; Azzahra Tiara Ramadhan; Abdul Aziz Syauqi; Bunga Ramadhani; Mia Salmiati; Mila Putika Jerni; Raisya Vio Lathifa; Rizky Kurniawan; Tasya Adriani (Universitas Methodist Indonesia, 2022)
The Purpose of this journal is to provide broader knowledge related to stunting prevention efforts by the use of appropriate food in the form of Moringa leaves which are easily available and economical. Stunting is a condition of failure to grow in toddlers so that it has an impact on the child's height that is not in accordance with his age. The main factor causing stunting is chronic malnutrition, especially in the first 1,000 days of a toddler's life. Activities carried out by Kukerta students include, firstly, making socialization related to what stunting is, why stunting should be considered, causes of stunting, how to prevent stunting with the method of the first 1000 days of life, stunting prevention efforts with a focus on increasing Moringa leaves. The next activity is to collect data on stunting children in Pancur Jaya Village to see how big the stunting rate is and to what extent it can be prevented from spreading. The third activity carried out was making and distributing Moringa leaf pudding as a nutritious food for the community and children of Pancur Jaya Village so that they get nutritious food that has been processed using Moringa leaves so that they are ready to eat. Another activity is planting Moringa seeds at several points in Pancur Jaya Village. Next is the distribution of Moringa leaf seeds to be planted around the homes of each resident of Pancur Jaya Village so that the results can be utilized in the context of preventing stunting and processed various nutritious foods. And the last activity is making Moringa porridge and distributing porridge to be consumed and become a reference for processed nutritious food for the community.